Value Co-Creation in the Sharing Economy Platform: The Role of Ethical Perceptions - Tjokrosaputro, Miharni (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2021)
This study aims to determine the effects of consumer participation on value co-creation with consumers’ ethical perceptions as a mediation of the sharing economy platform in Indonesia. The research design used a quantitative method with a descriptive approach. The sampling technique used convenience sampling with 287 respondents. A questionnaire was utilized as the data collecting technique. SmartPLS was applied as the analysis tool. The results showed that consumer participation has a significant effect on ethical perceptions and value co-creation and ethical perceptions affect value co-creation significantly. Furthermore, this research proof that ethical perceptions mediate the positive relationship between value co-creation on the sharing economy platform in Indonesia. This research enrich and strengthen the role of consumer ethical perceptions and consumer participation in creating value co-creation that provides value for both consumers and service providers based on Service-Dominant Logic (Vargo and Lusch, 2008).